Roles of immune microenvironment in the female reproductive maintenance and regulation: novel insights into the crosstalk of immune cells - Dai, Mengyuan; Xu, Ying; Gong, Guidong; Zhang, Yaoyao (Frontiers in Immunology, 2023)
Female fertility decline is an accumulative consequence caused by complex factors, among them, the disruption of the immune profile in female reproduction stands out as a crucial contributor. Presently, the effects of immune microenvironment (IME) on the female reproductive process have attracted increasing attentions for their dynamic but precisive roles. Immunocytes including macrophages, dendritic cells, T cells, B cells and neutrophils, with diverse subpopulations as well as high plasticity functioned dynamically in the process of female reproduction through indirect intercellular communication via specific cytokine release transduced by molecular signal networks or direct cell-cell contact to maintain the stability of the reproductive process have been uneviled. The immune profile of female reproduction in each stage has also been meticulously unveiled. Especially, the application of single-cell sequencing (scRNA-seq) technology in this process reveals the distribution map of immune cells, which gives a novel insight for the homeostasis of IME and provides a research direction for better exploring the role of immune cells in female reproduction. Here, we provide an all-encompassing overview of the latest advancements in immune modulation within the context of the female reproductive process. Our approach involves structuring our summary in accordance with the physiological sequence encompassing gonadogenesis, folliculogenesis within the ovaries, ovulation through the fallopian tubes, and the subsequent stages of embryo implantation and development within the uterus. Our overarching objective is to construct a comprehensive portrayal of the immune microenvironment (IME), thereby accentuating the pivotal role played by immune cells in governing the intricate female reproductive journey. Additionally, we emphasize the pressing need for heightened attention directed towards strategies that focus on immune interventions within the female reproductive process, with the ultimate aim of enhancing female fertility.